Blood Sisters : A Novel - Corry, Jane (New York, New York : Pamela Dorman Books, Viking, 2017)
Three little girls set off to school one sunny morning. Within an hour, one of them is dead. Fifteen years later, Kitty cant speak and has no memory of the accident thats to blame. She lives in an institution, unlikely ever to leave. But that doesnt keep her from being frightened when she encounters an eerily familiar face. Art teacher Alison looks fine on the surface. But the surface is a lie. Shes struggling to make ends meet and to forget the past. When a teaching job at a prison opens up, she takes it, despite her fears. Maybe this is her chance to set things right. Then she starts to receive alarming notes; next, her classroom erupts in violence. Meanwhile, someone is watching both Kitty and Alison. Someone who never forgot what happened that day. Someone who wants revenge. And only another life will do.
"First published in Great Britain by Penguin Books, an imprint of Penguin Random House UK"--Verso.
Keywords: Revenge -- Fiction; Murder -- England; Fiction; Girls -- Crimes against; Fiction; Prisons -- England; Fiction; Thrillers (Fiction)